Nonspreading Rift Valley Fever Virus Infection of Human Dendritic Cells Results in Downregulation of CD83 and Full Maturation of Bystander Cells - Oreshkova, Nadia (PLoS One, 2015)
Vaccines based on nonspreading Rift Valley fever virus (NSR) induce strong humoral and robust cellular immune responses with pronounced Th1 polarisation. The present work was aimed to gain insight into the molecular basis of NSR-mediated immunity. Recent studies have demonstrated that wild-type Rift Valley fever virus efficiently targets and replicates in dendritic cells (DCs). We found that NSR infection of cultured human DCs results in maturation of DCs, characterized by surface upregulation of CD40, CD80, CD86, MHC-I and MHC-II and secretion of the proinflammatory cytokines IFN-β, IL-6 and TNF. Interestingly, expression of the most prominent marker of DC maturation, CD83, was consistently downregulated at 24 hours post infection. Remarkably, NSR infection also completely abrogated CD83 upregulation by LPS. Downregulation of CD83 was not associated with reduced mRNA levels or impaired CD83 mRNA transport from the nucleus and could not be prevented by inhibition of the proteasome or endocytic degradation pathways, suggesting that suppression occurs at the translational level. In contrast to infected cells, bystander DCs displayed full maturation as evidenced by upregulation of CD83. Our results indicate that bystander DCs play an important role in NSR-mediated immunity.